Retrospective Study of the Significant Predictive Role of Inflammatory Degree in Initial and Repeat Prostate Biopsy Specimens for Detecting Prostate Cancer - Kim, Sung Han; Park, Boram; Joung, Jae Young; Chung, Jinsoo; Seo, Ho Kyung; Lee, Kang Hyun; Park, Weon Seo (Cancer research and treatment, 2019)
The purpose of this study was to determine whether histologic inflammation (HI) in initial and repeat prostate biopsy specimens was significantly associated with the detection of prostate cancer. Between 2005 and 2017, the clinicopathological records of patients with high prostatespecific antigen (PSA) levels who underwent initial and repeat prostate biopsies were retrospectively reviewed. The presence of HI and its degree in each biopsied specimen were interpreted by one uropathologist with 20 years of experience. The association between HI and cancer diagnosis was statistically assessed, with p < 0.05 considered significant, and the cancer and non-cancer groups were compared. Among the 522 patients with a median PSA levels of 6.5 ng/dL, including 258 (49.4%) whose cancer was diagnosed following repeat biopsy, the median degrees of HI in the initial and repeat biopsies were 25.0% and 41.7%, respectively. Furthermore, 211 (40.4%) and 247 (47.3%) patients had HI (> 0%) on biopsied specimens, respectively. Comparison of the cancer and noncancer groups revealed that a greater rate of HI specimens in the initial biopsy was associated with fewer prostate cancer diagnoses following repeat biopsy (p < 0.001). Other comparisons between the cancer and non-cancer groups showed that the cancer group had a significantly higher rate of hypertension, whereas those non-cancer group had a significantly higher rate of benign prostatic hyperplasia and prostatitis (p < 0.05). A finding of a lesser degree of HI in the initial and a greater degree of HI in the repeat biopsied specimens was associated with the higher probability of cancer diagnosis in patients with high PSA levels.